Reflection as a component of formative assessment appears to be instrumental in promoting the use of feedback; an observational study. (27th June 2013) - Pelgrim, E.A.M.; Kramer, A.W.M.; Mokkink, H.G.A.; van der Vleuten, C.P.M.
Abstract : Background : Although the literature suggests that reflection has a positive impact on learning, there is a paucity of evidence to support this notion. Aim : We investigated feedback and reflection in relation to the likelihood that feedback will be used to inform action plans. We hypothesised that feedback and reflection present a cumulative sequence (i.e. trainers only pay attention to trainees' reflections when they provided specific feedback) and we hypothesised a supplementary effect of reflection. Method : We analysed copies of assessment forms containing trainees' reflections and trainers' feedback on observed clinical performance. We determined whether the response patterns revealed cumulative sequences in line with the Guttman scale. We further examined the relationship between reflection, feedback and the mean number of specific comments related to an action plan (ANOVA) and we calculated two effect sizes. Results : Both hypotheses were confirmed by the results. The response pattern found showed an almost perfect fit with the Guttman scale (0.99) and reflection seems to have supplementary effect on the variable action plan. Conclusions : Reflection only occurs when a trainer has provided specific feedback; trainees who reflect on their performance are more likely to make use of feedback. These results confirm findings and suggestions reported in the literature.